Utilization of Instagram as a Marketing Communication Media for Dhy Hijab Fashion Store - Ulfi Nurfaiza (Fakultas Usluhuddin dan Dakwah IAIN Kediri, 2024)
Abstract Marketing products on digital platforms certainly cannot be separated from the use of strategies and the right role of marketers. This is exploited by one of the fashion stores, namely Dhy Hijab, which uses Instagram as a marketing medium for its products. The aim of this research is to find out the use of Instagram which was chosen as a marketing medium by Store Dhy Hijab. This research uses a descriptive qualitative method, which emphasizes a detailed discussion of the objects studied and arranged in a scientific setting. The theory used in this research is the theory used in this research is the Integrated Marketing Communication (IMC) marketing communication mix theory. The final result of this research is product marketing carried out by Dhy Hijab using 8 marketing communication mix tools, namely advertising, sales promotion, public relations and publications, personal selling, direct marketing, interactive marketing, word of mouth marketing, and events. Through the marketing communication mix activities carried out by Dhy Hijab, Dhy Hijab can maintain its business amidst the high competition in the fashion business sector.